The Effect of the Life Satisfaction of Individuals Over 65 Years on Their Happiness - Sermin Ağralı Ermiş; Ebru Dereceli (Selcuk University, 2023)
In our study, it was aimed to examine the effect of life satisfaction of individuals over 65 years of age on the happiness according to some demographic variables. 410 women and 399 men over 65 years of age participated in the study. The measurement tool to be used in the study was delivered to the participants via ' Google Form' and it was paid attention that they participated voluntarily. It was administered to 834 people in total and 809 scales were deemed suitable for analysis. The life satisfaction scale, which was developed by Diener et al. (15) and adapted into Turkish by Dagli and Baysal (10), and the happiness scale which was adapted by Demirci, İ.and Ekşi, H. (12), were used as data collection tools in the study. Descriptive statistics, reliability analysis, independent sample t test for binary variables, ANOVA test and Benferonni analysis for more than two variables were applied in the analysis of the data. As a result, according to the statistical results of the participants, it is seen that their happiness levels (x̄=19.90) and life satisfaction levels are high (x̄=15.72). It was determined that there was a high level of positive correlation between the life satisfaction of the participants and their happiness levels (r=0.723). As a result of the ANOVA analysis performed between life satisfaction and happiness levels and the variables of doing sports and sedentary life, it is seen that there are statistically significant differences (p<0.05).